Penguatan Safety Culture sebagai Strategi Manajemen Keselamatan Kerja pada kru KM. Kendhaga Nusantara 14 - Salna Taba Auliya Senja; Nina Ruly Istiari; Doni Hadi Irawan; Geri Damayanto (CV. Lentera Literasi Indonesia, 2026)
PT Citrabaru Adinusantara operates cargo, pioneer, and container vessels, including KM Kendhaga Nusantara 14, where occupational accidents remain a potential risk. This study aims to analyze the factors causing occupational accidents among the crew of KM Kendhaga Nusantara 14, with a focus on the accident that occurred on September 26, 2025. A descriptive qualitative method was employed using a snowball sampling technique. Data were collected through observation, documentation, and triangulation. The findings indicate that occupational accidents were mainly caused by low safety awareness, negligence, and lack of discipline in complying with safety procedures. These factors occurred despite the company having implemented Standard Operating Procedures (SOPs), provided Personal Protective Equipment (PPE), conducted safety meetings, and carried out work supervision. Preventive measures include strengthening compliance with SOPs, improving supervision, providing regular safety training, conducting risk assessments, and fostering a stronger safety culture to minimize occupational accidents.